Transglutamination allows production and characterization of native‐sized ELPylated spider silk proteins from transgenic plants. Issue 2 (16th November 2013) - Weichert, Nicola; Hauptmann, Valeska; Menzel, Matthias; Schallau, Kai; Gunkel, Philip; Hertel, Thomas C.; Pietzsch, Markus; Spohn, Uwe; Conrad, Udo
Summary In the last two decades it was shown that plants have a great potential for production of specific heterologous proteins. But high cost and inefficient downstream processing are a main technical bottleneck for the broader use of plant‐based production technology especially for protein‐based products, for technical use as fibres or biodegradable plastics and also for medical applications. High‐performance fibres from recombinant spider silks are, therefore, a prominent example. Spiders developed rather different silk materials that are based on proteins. These spider silks show excellent properties in terms of elasticity and toughness. Natural spider silk proteins have a very high molecular weight, and it is precisely this property which is thought to give them their strength. Transgenic plants were generated to produce ELPylated recombinant spider silk derivatives. These fusion proteins were purified by Inverse Transition Cycling (ITC) and enzymatically multimerized with transglutaminase in vitro. Layers produced by casting monomers and multimers were characterized using atomic force microscopy (AFM) and AFM‐based nanoindentation. The layered multimers formed by mixing lysine‐ and glutamine‐tagged monomers were associated with the highest elastic penetration modulus.